Modern family. The complete second season [videorecording (DVD)] - O'Neill, Ed, 1946-; Vergara, Sofía, 1972-; Bowen, Julie; Burrell, Ty, 1967- (20th Century Fox Home Entertainment, 2011)
"A refreshingly hilarious look at what it means to be a family in today's hectic, unpredictable world. While fledgling fathers Cameron and Mitchell struggle with learning the ropes of parenthood, longtime parents Claire and Phil try to keep the spice in their marriage amid the chaos of raising three challenging children. Meanwhile, family patriarch Jay has more than his hands full with his sexy, spirited wife, Gloria, and her precocious son."--Container.